Complete response to short‐term sorafenib treatment alone for hepatocellular carcinoma with bone, lymph node, and peritoneum metastases. Issue 13 (30th April 2016) - Nakano, Norihito; Kawaoka, Tomokazu; Aikata, Hiroshi; Honda, Fumi; Nakamura, Yuki; Morio, Kei; Hatooka, Masahiro; Fukuhara, Takayuki; Kobayashi, Tomoki; Hiramatsu, Akira; Imamura, Michio; Kawakami, Yoshiiku; et al.
Abstract : We report a 60‐year‐old male patient who developed extrahepatic metastases in bone, peritoneum, and lymph nodes (confirmed by computed tomography and positron emission tomography–computed tomography) after hepatectomy for hepatocellular carcinoma. He was treated with sorafenib (800 mg/day) but developed grade 3 hand–foot syndrome. He continued to be treated with sorafenib but at a lower dose (400 mg/week). The response to sorafenib therapy was graded as complete response at 6 months by the Response Evaluation Criteria in Solid Tumors. Sorafenib was continued for 8 months and the patient remained in complete response for 11 months. Further reporting of similar cases should help design treatment strategies and evaluate predictors of the response to sorafenib therapy.